Prova ilícita no processo civil - Cabeleira, Carlos Vinicius Soares (2010)
This essay studies the illegal evidence in the Brazilian Civil Procedure from the opposition between the constitutional right to produce evidence, due to the right of access to justice, and the Exclusionary Rule of illegal evidence, resulting from due process of law. Illegal evidence is the one that is the result of transgression of substantive law rules, in opposition to illegitimate evidence, in which there is violation of procedural rules. The consequences for each one is different: while the Constitution renders inadmissibility for the first, law sets nullity as sanction for the second. The distinction, which is largely accepted by the Brazilian doctrine, is connected with the division made by the legal theory between norms of conduct and norms of competence, so that the legal consequences of violation of each type of standards differ. Law 11.690/2008 has regulated article 5 section LVI 5 of the Constitution through the amendment of the Code of Criminal Procedure. This regulation also applies to Civil Procedure, adapted as necessary, because the differences between the two branches of procedural law. Analyzes the ―fruits of the poisonous tree doctrine‖ and the procedural consequences of recognizing the wrongfulness of evidence. Then, leaning back in the general theory of law, examines the issue of illegality and sanction, as well as legal excuses, to conclude that when the wrongfulness of conduct from which it originated evidence is excluded the evidence thus obtained should be lawful for all purposes. The question of the applicability of legal excuses is the first analysis of proportionality that can lead to non exclusion of evidence initially charged as illegal. If the unlawful act committed is not sheltered by any legal excuse, it is still possible not apply the penalties for illegal evidence, as the institutes of estoppel and curative acts, as well as the principles of ―no nullity without damages‖ and of the adversary system, connected to the nullity theory should also be applied to illegally obtained evidence, for the identity of reason. Finally, the illegal evidence can be also used through the application of proportionality, to prevent a fundamental right to suffer a more serious violation than that committed by unlawful obtaining of evidence, since all fundamental rights should be implemented in most extent possible. The application of proportionality, however, should be done with responsability, through grounding in the features of the case and following the method recommended by the doctrine through the subprinciples, sequentially considered, the appropriateness, necessity and proportionality in the strict sense.